2022
DOI: 10.1101/2022.05.17.492361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APOE modulates microglial immunometabolism in response to age, amyloid pathology, and inflammatory challenge

Abstract: SummaryThe E4 allele of Apolipoprotein E (APOE) is associated with both metabolic dysfunction and a heightened pro-inflammatory response – two findings that may be intrinsically linked through the concept of immunometabolism. Here, we combined bulk, single-cell, and spatial transcriptomics with cell-specific and spatially resolved metabolic analyses to systematically address the role of APOE across age, neuroinflammation, and AD pathology. RNAseq highlighted immunometabolic changes across the APOE4 glial trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…8C ). Furthermore, using recently published subtype-specific vascular marker genes (Vanlandewijck et al ., 2018; Barisano et al ., 2022; Lee et al ., 2022), distinct cell clusters were identified, including smooth muscle cells (SMC), vascular leptomeningeal cells, pericytes, endothelial cells, and astrocytes ( Fig. 8D-E ).…”
Section: Resultsmentioning
confidence: 99%
“…8C ). Furthermore, using recently published subtype-specific vascular marker genes (Vanlandewijck et al ., 2018; Barisano et al ., 2022; Lee et al ., 2022), distinct cell clusters were identified, including smooth muscle cells (SMC), vascular leptomeningeal cells, pericytes, endothelial cells, and astrocytes ( Fig. 8D-E ).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent investigations in animal models of AD support our findings. For example, the APOE genotype modulates microglial response in AD, with APOEε4 being associated with multiple microglial-related detrimental downstream effects (e.g., protein aggregation, neurodegeneration, and dysfunctional immunometabolic response) (25,(27)(28)(29)(30). Further experiments showed that the APOEε4 genotype associates with changes in the transcriptional profile of microglia from a homeostatic state to a disease-associated state across AD progression (31,32) and that the activation of microglial-related proteins [e.g., triggering receptor expressed on myeloid cells 2 (TREM2); (33)(34)(35)(36)] is directly associated with ApoE signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent animal studies suggest that the APOEε4 genotype may also contribute to AD pathogenesis through Aβ-independent pathways by potentiating brain inflammation, tau accumulation, and neurodegeneration (25,26). Although robust experimental evidence indicates that the APOE genotype modulates microglial response in AD (25,(27)(28)(29)(30), it remains to be elucidated whether the presence of the APOEε4 allele is associated with microglial activation in the AD human brain. The characterization of this association in living individuals is critical to confirm the Aβ-independent detrimental effects of APOEε4 on microglia homeostasis and to support the development of therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the APOE genotype modulates microglial response in AD, with APOE ε4 being associated with multiple microglial-related detrimental downstream effects ( e . g ., protein aggregation, neurodegeneration, and dysfunctional immunometabolic response) (25, 27-30) . Further experiments showed that the APOE ε4 genotype associates with changes in the transcriptional profile of microglia from a homeostatic state to a disease-associated state across AD progression (31, 32) and that the activation of microglial-related proteins ( e .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent animal studies suggest that the APOE ε4 genotype may also contribute to AD pathogenesis through Aβ-independent pathways by potentiating brain inflammation, tau accumulation, and neurodegeneration (25, 26) . Although robust experimental evidence indicates that the APOE genotype modulates microglial response in AD (25, 27-30) , it remains to be elucidated whether APOE ε4 carriership is associated with microglial activation in the AD human brain. The characterization of this association in living individuals is critical to confirm the Aβ-independent detrimental effects of APOE ε4 on microglia homeostasis and to support the development of novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%